Erythrodermic Manifestation due to Hyperinfestation of Scabies - Sandra Widaty; Martinus Martinus; Yenny Rachmawati (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Scabies is a highly contagious skin disease with various skin clinical presentations. In consideration of its clinical presentations, proper early-onset diagnosis of scabies may not be met, leading to mistreatment and more severe scabies, Norwegian (crusted) scabies. Purpose: To report a case of Norwegian scabies misdiagnosed as eczema in a previously immunocompetent patient. Case: A 32-year-old man was admitted with generalized erythematous skin rash, pruritic, and hyperkeratotic scales of the body. He was previously diagnosed with eczema two months ago and was prescribed both topical and systemic steroid. Skin scales worsened and kept expanding after the treatment. There was a family history of nocturnal itch. Dermoscopic and microscopic examination from skin lesion and scraping with potassium hydroxide revealed the signs of scabies infection. Discussion: Norwegian scabies could be prevented by the correct diagnosis at the early-onset of the disease. Misdiagnosis due to various skin clinical presentations, leading to mistreatment of the infection. In this case, family history plays a role that could elucidate the presence of scabies infection. Conclusion: A correct diagnosis and treatment for the early-phase scabies-infected patient will be beneficial for the patient to prevent hyperinfestation of scabies mites. Specific examination for scabies decreases the possibility of misdiagnosis.